A History of Scottish Economic Thought - Dow, Alexander Dow; Dow, Sheila (The Routledge History of Economic Thought, 2006)
Modern economics has, at its foundation, scholarly contributions from many prominent Scottish thinkers. This revealing work examines the roots of this great tradition, places in perspective a selection of authors, and assesses their contribution over three centuries in the light of a distinctive Scottish approach to economics. Scottish Enlightenment is an established area of research interest, and this volume offers new scholarship on key Enlightenment figures whilst placing emphasis on their approach to economic thought. Smith and Hume are key, but other less familiar, yet important authors are also investigated here, including a murderer, a revolutionary, a medical practitioner and a novelist (John Law, Sir James Stuart, John Rae and Shield Nicholson, respectively). The latest in a prestigious series charting national traditions in the history of economic thought, this important book, an essential read for scholars of economic thought, features contributions from such major historians of economic thought as Andrew Skinner and Antoin Murphy.